2009
DOI: 10.1111/j.1365-2966.2009.15016.x
|View full text |Cite
|
Sign up to set email alerts
|

Fermion zero-mode influence on neutron-star magnetic field evolution

Abstract: The quantum phenomenon of spectral flow which has been observed in laboratory superfluids, such as 3He-B, controls the drift velocity of proton type II superconductor vortices in the liquid core of a neutron star and so determines the rate at which magnetic flux can be expelled from the core to the crust. In the earliest and most active phases of the anomalous X-ray pulsars and soft-gamma repeaters, the rates are low and consistent with a large fraction of the active crustal flux not linking the core. If norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The frictional force on a flux tube due to scattering of zero modes localized inside the flux tube off gapless fermions in the bulk [44,45] has been calculated for proton flux tubes in nuclear matter [33]. At low temperatures, we expect the frictional force on a 2SC flux tube to be…”
Section: F Zero-mode Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The frictional force on a flux tube due to scattering of zero modes localized inside the flux tube off gapless fermions in the bulk [44,45] has been calculated for proton flux tubes in nuclear matter [33]. At low temperatures, we expect the frictional force on a 2SC flux tube to be…”
Section: F Zero-mode Forcementioning
confidence: 99%
“…(There is controversy about this in the literature; for example, Jones [33,43] has suggested that this is cancelled by another contribution from ungapped fermions. Pending a definitive resolution of this disagreement we will use the standard form of the Magnus-Lorentz force.…”
Section: Magnus-lorentz Forcementioning
confidence: 99%
“…The existence of fermion degrees of freedom is also important at the macroscopic level, as pointed out by Jones 66 . As is known in superfluid and superconducting systems, fermion bound states in the vortex core seriously affect vortex dynamics through the spectral flow force [67][68][69] .…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, such a braking index can be accounted for if the magnetic dipole braking still dominates but the star is experiencing a long-term dipole magnetic field decay. The surface dipole magnetic field has a significant effect on the spin evolution of a pulsar, as well as on its braking index (e.g., Goldreich & Reisenegger 1992;Tauris & Konar 2001;Jones 2009;Marchant et al 2014). In the case of a varying dipole magnetic field at the pole B p , the braking index n can be simply expressed as follows: Kaminker et al 2014;Potekhin et al 2015), whereas n 3 < for an increasing B p (e.g., Mereghetti 2008;Gao et al 2016).…”
Section: Introductionmentioning
confidence: 99%